2023
DOI: 10.3390/ma16093320
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Investigation of the Surface Properties of Corn-Starch-Microfibrillated Cellulose Composite Films

Abstract: Starch-based materials seem to be an excellent alternative for conventional plastics used in various applications. Microfibralted cellulose can be used to improve the surface properties of starch-based materials. This study aims to analyze the surface properties of starch-microfibrillated cellulose materials. The surface properties of films were evaluated by ATR-FTIR, surface roughness, water wettability, and surface free energy. The surface homogeneity between corn starch and microfibrillated cellulose (MFC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 49 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…An increase was observed in the presence of bleached and unbleached nanofibers and a decrease in the presence of nanocrystals. The addition of microfibrillated cellulose (MFC) increased the surface roughness and polarity of the starch/MFC materials developed [ 90 ]. Velásquez-Castillo et al (2023) reported that in starch films reinforced with 5.0 and 7.5 wt% quinoa starch nanocrystals [ 91 ], roughness increased with the presence of nanocellulose.…”
Section: Resultsmentioning
confidence: 99%
“…An increase was observed in the presence of bleached and unbleached nanofibers and a decrease in the presence of nanocrystals. The addition of microfibrillated cellulose (MFC) increased the surface roughness and polarity of the starch/MFC materials developed [ 90 ]. Velásquez-Castillo et al (2023) reported that in starch films reinforced with 5.0 and 7.5 wt% quinoa starch nanocrystals [ 91 ], roughness increased with the presence of nanocellulose.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed the procedure in our works, for example, see [36]. The reagents (10 g of starch, 5 g of glycerol in 200 g of water) were heated up to 95 • C upon stirring with a mechanical stirrer and cast onto Teflon ® plates placed on a K Paint Applicator (RK Print, Royston, UK) equipped with an adjustable micrometer spreader gap set to 3 mm with a constant coating speed (6 m•min −1 ).…”
Section: Film Preparationmentioning
confidence: 99%
“…It is worth remembering that PLA also has some limitations. It is a relatively brittle material compared to some other materials [21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%